Thoracodorsal artery flaps for breast reconstruction–the variants and its approach - Thomsen, Jørn Bo; Rindom, Mikkel Børsen; Rancati, Alberto; Angrigiani, Claudio (Archives of Plastic Surgery, 2021)
Thoracodorsal artery (TDA) flaps, ranging from the vascular-pedicled thoracodorsal artery perforator (TDAP) flap, the propeller TDAP flap, and the muscle-sparing latissimus dorsi (MSLD) flap to the conventional latissimus dorsi (LD) flap and the extended LD flap, can all be used for breast reconstruction. The aim of this paper and review is to share our experiences and recommendations for procedure selection when applying TDA-based flaps for breast reconstruction. We describe the different surgical techniques and our thoughts and experience regarding indications and selection between these procedures for individual patients who opt for breast reconstruction. We have performed 574 TDA flaps in 491 patients: 60 extended LD flaps, 122 conventional LD flaps, two MSLD flaps, 233 propeller TDAP flaps, 122 TDAP flaps, and 35 free contralateral TDAP flaps for stacked TDAP breast reconstruction. All the TDA flaps are important flaps for reconstruction of the breast. The LD flap is still an option, although we prefer flaps without muscle when possible. The vascular-pedicled TDAP flap is an option for experienced surgeons, and the propeller TDAP flap can be used in most reconstructive cases of the breast, although a secondary procedure is often necessary for correction of the pedicle bulk. The extended LD flap is an option for women with a substantial body mass index, although it is associated with the highest morbidity of all the TDA flaps. The MSLD flap can be used if the perforators are small or if dissection of the perforators is assessed to be hazardous.
Keywords: Keywords; Breast; Surgical flaps; Education, medical